On the Crimea-Texas project "Surface abundances of light elements for a large sample of early B-type stars". - Lyubimkov, L. S. (Одеські астрономічні публікації, 2017)
A significant part of the project is already implemented. Actually, high-resolution spectra of more than 100 early B stars were obtained. A number of basic parameters was determined including the effective temperatures Teff , surface gravities log g, masses M, ages t etc. A detailed non-LTE analysis of HeI lines was effected to find the helium abundance He/H, microturbulent parameter Vt and rotational velocity v sin i . Relations between He/H and Vt , from the one hand, and M, t/tms and v sin i , from the other hand, were constructed. It was confirmed that there is the helium enrichment during the MS phase, which correlates with the masses M and rotational velocities v sin i . It is necessary to note that from the outset we tried to get a highest accuracy on each stage of this work. At present we are implementing a last stage of the project, i.e. an analysis of CII, NII and OII lines on the basis of non-LTE computations. Our goal is an accurate determination of the C, N and O abundances and a search for correlations with M, t/tms and v sin i.